PERAN FINTECH SYARIAH DALAM PEMBERDAYAAN UMKM DI DESA TUGUMULYO - Jesnita Fitri Novalia; Saiful Bakhri (Universitas KH. Mukhtar Syafaat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Tugumulyo Village play a strategic role in driving local economic dynamics. However, their development remains constrained by limited access to business capital, low financial management capacity, and minimal utilization of digital technology in business operations. The emergence of Islamic financial technology (Islamic fintech) offers an alternative solution aligned with the principles of Islamic economics, through the provision of inclusive, transparent, and sharia-compliant financial services. This study aims to analyze the role of Islamic fintech in empowering MSMEs in Tugumulyo Village, particularly in terms of financing access, operational efficiency, and market expansion. A quantitative approach with a survey method was employed, targeting MSME actors who have utilized Islamic fintech services. The findings indicate that Islamic fintech significantly contributes to improving financing accessibility for MSMEs, facilitating digital financial transactions, and supporting more structured cash flow management. On the other hand, the extent of Islamic fintech utilization remains varied and uneven, influenced by differences in Islamic financial literacy levels, digital infrastructure readiness, and the adaptive capacity of business actors toward technological innovation. Therefore, strengthening a collaborative digital ecosystem among the government, Islamic fintech service providers, and MSME actors is essential to enhance competitiveness and business sustainability at the village level. This study recommends the need for enhanced Islamic financial education and the development of digital infrastructure to accelerate technology-based MSME transformation in rural areas. Keywords: Islamic fintech, MSME empowerment, financing access, Islamic financial literacy, digital transformation